If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(5 + 4b) + -2 = 0 (5 * 3 + 4b * 3) + -2 = 0 (15 + 12b) + -2 = 0 Reorder the terms: 15 + -2 + 12b = 0 Combine like terms: 15 + -2 = 13 13 + 12b = 0 Solving 13 + 12b = 0 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + 12b = 0 + -13 Combine like terms: 13 + -13 = 0 0 + 12b = 0 + -13 12b = 0 + -13 Combine like terms: 0 + -13 = -13 12b = -13 Divide each side by '12'. b = -1.083333333 Simplifying b = -1.083333333
| 3z-4=5z-1 | | 4+a=16 | | 82=2(-1+7m) | | 7+3.2=3.2x | | 2b+8=0 | | 6y-4(2-3(4y-1))=-17 | | A+81=9z-7 | | 7b+13=35-4b | | 166=2*36+2W | | 27x^2+37x=0 | | 3=2(-2)-y | | 4x-12=3.5 | | 10+x=1x+2 | | 3(x+4)-2=3x+10 | | 2x-4y+-6=0 | | 6y+15=9y | | 2u+10=20 | | 3b*c= | | 2x^3-12x^2+24x-14=0 | | 8x-x^2-15=0 | | 2x+4=8x-1 | | y+3=4(x-1) | | t^2+3tf-28f^2= | | 2x^3+2x-12=0 | | 15x-4z=20 | | 4.08(x+10)=9.50(x-2) | | 2y-8=7y+17 | | 3(r-6)+2=2(r+2)-21 | | 2(9n-1)+7(10+x)=35 | | 9x^8+18x^6=0 | | U-9=-7u+7-9 | | 2x=4(x+34) |